Wykonaj odejmowanie. a) (3xy-5x*)-(10xy-2x*y) b) (-12abc-4a*bc)-(abc+a*bc)+12 c)(1 3/5x do sześcianu+2/3y*-5/6)-2,4xdo sześcianu+y*-1 1/6)       DAJE NAJ A TO * OZNACZA DO KWADRATU  

Wykonaj odejmowanie. a) (3xy-5x*)-(10xy-2x*y) b) (-12abc-4a*bc)-(abc+a*bc)+12 c)(1 3/5x do sześcianu+2/3y*-5/6)-2,4xdo sześcianu+y*-1 1/6)       DAJE NAJ A TO * OZNACZA DO KWADRATU  
Odpowiedź
michal0124

a)-7xy-5x*-2x*y

pawcio10

a) (3xy-5x*)-(10xy-2x*y) = 3xy -  5x² - 10xy + 2x²y = -7xy - 5x² + 2x²y b) (-12abc-4a*bc)-(abc+a*bc)+12  = -12abc - 4a²bc - abc - a²bc = -13abc - 5a²bc c)(1 3/5x do sześcianu+2/3y*-5/6)-2,4xdo sześcianu+y*-1 1/6) = 8/5x³ - 5/9y² - 12/5x³ - 7/6y² = -4/5x³ - 10/18y² - 21/18y² = -4/5x³ - 31/18y² = -4/5x³ - 1 13/18y²

Dodaj swoją odpowiedź